Catalyst degradation method
By treating the catalyst with organic acid, water and oxygen, and reacting with inert gas and olefins, the deterioration of the catalyst is achieved, which solves the problem of inefficient catalyst development, improves screening efficiency and reduces costs.
Patent Information
- Application Number
- CN202411339843.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art is difficult to quickly screen and evaluate the service life of catalysts, resulting in inefficient catalyst development and increased costs.
The fresh catalyst is treated with organic acid, water and oxygen in the reactor, and then dried with inert gas and reacted with C3-C6 olefins, acetic acid, water and oxygen, and finally inert gas and acetic acid are introduced to achieve the deterioration treatment of the catalyst.
Accelerate the agglomeration of active catalyst components and surface polymer generation, realize rapid deactivation of the catalyst, facilitate rapid screening and renewal, reduce the cost and energy consumption in the catalyst evaluation process, and improve development efficiency.
Smart Images

Figure CN119310223A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts and relates to a method for catalyst deterioration, in particular to a method for acetyl oxidation catalyst deterioration. Background Art
[0002] Vinyl acetate is an important organic synthesis intermediate. Typical vinyl acetates include vinyl acetate, allyl acetate, methacrylic acetate, etc. Among them, allyl acetate is a colorless, flammable liquid that is slightly soluble in water, easily soluble in alcohol and ether, and soluble in acetone. As an important chemical raw material, it is mainly used in the production of important organic synthesis raw materials such as allyl alcohol, epichlorohydrin, glycerol, and is also used in the synthesis of resins and adhesives.
[0003] The industrial production of vinyl acetate is synthesized by gas-phase catalytic reaction on a palladium catalyst with C2-C4 olefins, oxygen and acetic acid as raw materials. The activity of the catalyst gradually decreases during industrial application, and the catalyst deactivation occurs. The catalyst life evaluation during the catalyst development process requires a long operating time, which affects the development efficiency of the catalyst. The decrease in the activity of the acetyl oxidation catalyst is mainly due to the growth of the metal grains of the active component palladium and the coverage of the active components on the catalyst surface by polymers, which leads to a gradual decrease in the activity of the catalyst.
[0004] Patent publication number CN1292726A discloses a method for slowing down the aging of vinyl acetate catalysts, which includes contacting a reactant gas with a catalyst containing palladium, gold and a carrier in the presence of clean steam, wherein the clean steam exists at a pressure of about 2 to about 10 psia, provided that the carrier does not contain aluminum oxide or zinc oxide, and the deactivation of the catalyst can be slowed down after treatment by this method, so that the activity of the Pd-Au system vinyl acetate catalyst can be restored. However, this patent only reports a method for slowing down the deactivation of vinyl acetate catalysts, and there are few reports on patents for accelerating catalyst deterioration.
[0005] Therefore, developing a suitable method to accelerate catalyst deactivation is conducive to rapid screening of catalysts and improving catalyst development efficiency. Summary of the invention
[0006] The present invention provides a catalyst degradation method. By performing degradation treatment on a fresh catalyst, the deactivation of the fresh catalyst can be accelerated, which is beneficial to evaluating the service life of the catalyst, facilitating rapid screening of the catalyst, and saving the development cost of the catalyst.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A method for catalyst degradation, the method comprising the following steps:
[0009] a) placing a fresh catalyst into a reactor, and introducing an organic acid, water and oxygen for treatment;
[0010] b) Drying by passing inert gas;
[0011] c) Enter C 3 -C 6 The reaction of olefins, acetic acid, water, inert gas and oxygen;
[0012] d) introducing an inert gas and acetic acid to obtain a degraded catalyst.
[0013] Furthermore, in step a), the fresh catalyst is a catalyst for acetyl oxidation, such as the catalyst disclosed in CN114054044B, and the patent contents disclosed in the catalyst can be cited as prior art in this patent. Preferably, the fresh catalyst comprises a carrier, an active metal and an additive, and the chemical composition of the carrier is SiO 2 and optionally Al 2 O 3 , Fe 2 O 3 or a mixture thereof, wherein the catalyst active component comprises metal palladium and optionally gold, copper, and tin, and the auxiliary agent is alkali metal acetate.
[0014] Furthermore, the palladium content in the fresh catalyst is 0.5-10 g / L, preferably 1.0-6.0 g / L; the gold content is 0-8 g / L, preferably 0-5 g / L; the copper content is 0-5 g / L, preferably 1-3 g / L; and the tin content is 0-3 g / L, preferably 0-2 g / L.
[0015] Furthermore, the alkali metal acetate is at least one of sodium acetate, potassium acetate and cesium acetate, preferably potassium acetate; the content of the alkali metal acetate is 10-100 g / L, preferably 20-80 g / L.
[0016] Further, in step a), the treatment is carried out at a reaction temperature of 100-300°C, preferably 120-200°C; and a pressure of 0.1-3MPa, preferably 0.3-1.5MPa; the organic acid is selected from at least one of formic acid, acetic acid, propionic acid, acrylic acid, butyric acid, and succinic acid, preferably acetic acid; the oxygen can be added in the form of pure oxygen or in the form of air; the volume concentration of the organic acid is 1-25%, preferably 5-20%, the volume concentration of water is 1-25%, preferably 5-20%, the volume concentration of oxygen is 0.5-10%, preferably 1-8%, and the remaining gas is nitrogen; the treatment time is 5-100h, preferably 10-80h.
[0017] Furthermore, in step b), the inert gas is at least one of nitrogen, helium, argon and carbon dioxide, preferably nitrogen and carbon dioxide; the drying temperature is 100-200° C., and the treatment time is 0.5-8 h, preferably 1-6 h.
[0018] Further, in step c), the C 3 -C 6 The olefin is at least one of propylene, isobutylene, butadiene, pentene and hexene, preferably propylene and isobutylene; the inert gas is at least one of nitrogen, helium, argon and carbon dioxide, preferably nitrogen and carbon dioxide; the C 3 -C 6 The feed molar ratio of olefin: acetic acid: water: oxygen: inert gas is 20-70: 4-20: 0-20: 1-10: 20-60; the reaction temperature is 120-200°C, the treatment time is 2-10h, the reaction pressure is 0.1-1.5MPa, preferably 0.3-1.0MPa; the space velocity is 500-4000h -1 , preferably 600-2500h -1 .
[0019] Furthermore, the inert gas in step d) is at least one of nitrogen, helium, argon and carbon dioxide, preferably nitrogen and carbon dioxide; the molar ratio of the inert gas to the acetic acid feed is 70-99:1-30.
[0020] The present invention has the following beneficial effects:
[0021] 1) The present invention accelerates the agglomeration of the active component grains of the catalyst and the generation of surface polymers by treating the catalyst for degradation, thereby achieving rapid deactivation of the catalyst, facilitating rapid screening of the catalyst, improving the efficiency of catalyst development, and promoting the replacement of the catalyst;
[0022] 2) This method can reduce the normal evaluation operation time of acetyl oxidation catalysts, reduce personnel, material costs and energy consumption in the catalyst evaluation process, reduce catalyst development costs, and improve industry competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Trend chart of STY value and shell side temperature and operation time during normal catalyst evaluation process;
[0024] Figure 2 The trend of the average crystal size of the active components in the normal catalyst evaluation process and the operating time. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, the embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.
[0026] The main raw material sources of the following examples are as follows:
[0027] Unless otherwise specified, all raw materials are commercially available
[0028] The main test methods involved in the following embodiments are as follows:
[0029] 1. Determination of particle size of active components of catalyst
[0030] The catalyst was crushed with a mortar to obtain a uniform powder, and then the catalyst powder was ultrasonically dispersed in anhydrous ethanol. The JEOL 2100plus transmission electron microscope (TEM) was used to measure the grain sizes of more than 300 active components and calculate the average grain size.
[0031] 2. Use gas chromatography and Agilent GC 8890A chromatograph to analyze the content of each component in the reaction product, and calculate the activity of the catalyst according to the following formula:
[0032] The calculation method of catalyst activity is:
[0033]
[0034] Normal evaluation of catalyst:
[0035] 500 mL of fresh catalyst was placed in a fixed bed reactor with an inner diameter of 3 cm and a height of 150 cm without any treatment. Inert porcelain balls were loaded at the upper and lower ends of the catalyst. After nitrogen leak testing, the reaction system was heated to 140 °C, and then the reaction raw materials were introduced. The reaction pressure was 0.75 MPaG and the volumetric space velocity was 2000 h -1 The raw gas phase composition is 40% propylene, 10.0% acetic acid, 7.0% oxygen, 33% nitrogen and 10% water. The initial reaction temperature is 140°C. By gradually increasing the reaction temperature, the space-time yield of the catalyst is maintained at 375-390. The cumulative operation time is 6000 hours. The operation time and the corresponding reaction temperature are recorded. Figure 1 The evaluated catalyst was sampled and analyzed every 500 hours to test the change trend of the grain size of the active components of the evaluated catalyst with the running time. Figure 2 .
[0036] [Example 1]
[0037] 1) Catalyst degradation
[0038] Take 500mL of fresh catalyst. Put the catalyst into a tubular fixed bed reactor, the reaction temperature is 150℃, the reaction pressure is 0.5MPa, the volume concentration of acetic acid is 15%, the volume concentration of water is 18%, the volume concentration of oxygen is 4.0%, and the rest is nitrogen, and the deterioration treatment is 40h; after the treatment, 4.5L / min of nitrogen is introduced and the treatment is carried out for 4h; under the conditions of reaction pressure of 0.7MPa, reaction temperature of 160℃, and total gas volume of 12.5L / min, the raw materials propylene: acetic acid: water: oxygen: nitrogen are fed in a molar ratio of 20:4:12:4:30, and the treatment is carried out for 10h; then the raw materials are replaced with acetic acid and nitrogen, the volume concentration of acetic acid is 6%, and the rest is nitrogen, and the treatment is carried out for 1h to obtain the deteriorated catalyst.
[0039] 2) Catalyst performance test
[0040] 500 mL of the degraded catalyst was placed in a fixed bed reactor with an inner diameter of 3 cm and a height of 150 cm. Inert porcelain balls were loaded at the upper and lower ends of the catalyst. After nitrogen leak testing, the reaction system was heated to 140 °C, and then the reaction raw materials were introduced. The reaction pressure was 0.75 MPaG and the volumetric space velocity was 2000 h -1 The raw gas phase composition is 40% propylene, 10.0% acetic acid, 7.0% oxygen, 33% nitrogen and 10% water. The reaction temperature is gradually increased to 154.6°C. The space-time yield of the catalyst is 383, which is equivalent to the normal evaluation of the catalyst for 3800 hours. The degraded catalyst was measured by transmission electron microscopy to count the grain sizes of 300 active components, with an average value of 8.7nm. The average grain size of the active components of the catalyst that has been running normally for 3800 hours is 8.5nm. The grain size of the degraded catalyst is basically consistent with the grain size of the catalyst after 3800 hours of normal evaluation.
[0041] [Example 2]
[0042] 1) Catalyst degradation
[0043] Take 500 mL of fresh catalyst and put it into a tubular fixed bed reactor. The reaction temperature is 143°C, the reaction pressure is 0.7 MPa, the volume concentration of acetic acid is 8%, the volume concentration of water is 14%, the volume concentration of oxygen is 5.0%, and the rest is nitrogen. The deterioration treatment is carried out for 24 hours. After the treatment, 4.5 L / min of carbon dioxide is introduced and the treatment is carried out for 6 hours. Under the conditions of reaction pressure of 1.0 MPa, reaction temperature of 150°C, and total gas volume of 8.3 L / min, the raw materials of isobutylene: acetic acid: water: oxygen: nitrogen are fed in a molar ratio of 30:6:12:6:43 and the treatment is carried out for 2 hours. Then the raw materials are replaced with acetic acid and nitrogen, the volume concentration of acetic acid is 10%, and the rest is nitrogen. The treatment is carried out for 3 hours to obtain a deteriorated catalyst.
[0044] 2) Catalyst performance test
[0045] 500 mL of the degraded catalyst was placed in a fixed bed reactor with an inner diameter of 3 cm and a height of 150 cm. Inert porcelain balls were loaded at the upper and lower ends of the catalyst. After leak testing with nitrogen, the reaction system was heated and then the reaction raw materials were introduced. The reaction pressure was 0.75 MPaG and the volumetric space velocity was 2000 h -1 The raw gas phase composition is 40% propylene, 10.0% acetic acid, 7.0% oxygen, 33% nitrogen and 10% water. The reaction temperature is gradually increased to 149.5°C. The space-time yield of the catalyst is 388, which is equivalent to the normal evaluation of the catalyst for 2575 hours. The degraded catalyst was measured by transmission electron microscopy to count the grain sizes of 300 active components, with an average value of 6.8nm. The average grain size of the active components of the catalyst that is normally operated for 2575 hours is 7.1nm. The grain size of the degraded catalyst is basically consistent with the grain size of the catalyst after 2575 hours of normal evaluation.
[0046] [Example 3]
[0047] 1) Catalyst degradation
[0048] Take 500 mL of fresh catalyst and put it into a tubular fixed bed reactor. The reaction temperature is 120°C, the reaction pressure is 0.3 MPa, the volume concentration of acetic acid is 5%, the volume concentration of water is 20%, the volume concentration of oxygen is 8.0%, and the rest is nitrogen. The deterioration treatment is carried out for 80 hours. After the treatment, 6 L / min of nitrogen is introduced and the treatment is carried out for 6 hours. Under the conditions of reaction pressure of 0.3 MPa, reaction temperature of 200°C, and total gas volume of 20.8 L / min, the raw materials propylene: acetic acid: water: oxygen: nitrogen are fed in a molar ratio of 40:15:20:2:50 and the treatment is carried out for 6 hours. Then the raw materials are replaced with acetic acid and nitrogen, the volume concentration of acetic acid is 30%, and the rest is nitrogen. The treatment is carried out for 3 hours to obtain a deteriorated catalyst.
[0049] 2) Catalyst performance test
[0050] 500 mL of the degraded catalyst was placed in a fixed bed reactor with an inner diameter of 3 cm and a height of 150 cm. Inert porcelain balls were loaded at the upper and lower ends of the catalyst. After leak testing with nitrogen, the reaction system was heated and then the reaction raw materials were introduced. The reaction pressure was 0.75 MPaG and the volumetric space velocity was 2000 h -1 The raw gas phase composition is 40% propylene, 10.0% acetic acid, 7.0% oxygen, 33% nitrogen and 10% water. The reaction temperature is gradually increased to 164.0℃. The space-time yield of the catalyst is 382, which is equivalent to the normal evaluation of the catalyst for 5382 hours. The degraded catalyst was measured by transmission electron microscopy to count the grain sizes of 300 active components, with an average value of 12.1nm. The average grain size of the active components of the catalyst that is normally operated for 5382 hours is 11.7nm. The grain size of the degraded catalyst is basically consistent with the grain size of the catalyst after 5382 hours of normal evaluation.
[0051] [Example 4]
[0052] 1) Catalyst degradation
[0053] Take 500 mL of fresh catalyst and put it into a tubular fixed bed reactor with a reaction temperature of 200°C, a reaction pressure of 1.5 MPa, an acetic acid volume concentration of 20%, a water volume concentration of 5%, an oxygen volume concentration of 1.0%, and the rest being nitrogen. The deterioration treatment is carried out for 10 hours. After the treatment, 4.5 L / min of nitrogen is introduced and the treatment is carried out for 3 hours. Under the conditions of a reaction pressure of 0.6 MPa, a reaction temperature of 120°C, and a total gas volume of 5.0 L / min, the raw materials propylene: acetic acid: water: oxygen: nitrogen are fed in a molar ratio of 50:10:16:8:47 and the treatment is carried out for 8 hours. Then the raw materials are replaced with acetic acid and nitrogen, the acetic acid volume concentration is 20%, and the rest is nitrogen. The treatment is carried out for 6 hours to obtain a deteriorated catalyst.
[0054] 2) Catalyst performance test
[0055] 500 mL of the degraded catalyst was placed in a fixed bed reactor with an inner diameter of 3 cm and a height of 150 cm. Inert porcelain balls were loaded at the upper and lower ends of the catalyst. After leak testing with nitrogen, the reaction system was heated and then the reaction raw materials were introduced. The reaction pressure was 0.75 MPaG and the volumetric space velocity was 2000 h -1The raw gas phase composition is 40% propylene, 10.0% acetic acid, 7.0% oxygen, 33% nitrogen and 10% water. The reaction temperature is gradually increased to 152.6°C. The space-time yield of the catalyst is 388, which is equivalent to the normal evaluation of the catalyst for 3295 hours. The degraded catalyst was measured by transmission electron microscopy to count the grain sizes of 300 active components, with an average value of 8.1nm. The average grain size of the active components of the catalyst that is normally operated for 3295 hours is 8.0nm. The grain size of the degraded catalyst is basically consistent with the grain size of the catalyst after 3295 hours of normal evaluation.
[0056] [Example 5]
[0057] 1) Catalyst degradation
[0058] Take 500 mL of fresh catalyst and put it into a tubular fixed bed reactor with a reaction temperature of 155°C, a reaction pressure of 0.6 MPa, an acetic acid volume concentration of 16%, a water volume concentration of 16%, an oxygen volume concentration of 3.5%, and the rest being nitrogen, and undergo deterioration treatment for 70 hours; after the treatment, introduce 5 L / min of nitrogen and treat for 5 hours; under the conditions of a reaction pressure of 0.6 MPa, a reaction temperature of 155°C, and a total gas volume of 16.6 L / min, the raw materials propylene: acetic acid: water: oxygen: nitrogen are fed in a molar ratio of 30:7.5:18:7:45 and treated for 5 hours; then the raw materials are replaced with acetic acid and nitrogen, the acetic acid volume concentration is 5%, and the rest is nitrogen, and the treatment is performed for 6 hours to obtain a deteriorated catalyst.
[0059] 2) Catalyst performance test
[0060] 500 mL of the degraded catalyst was placed in a fixed bed reactor with an inner diameter of 3 cm and a height of 150 cm. Inert porcelain balls were loaded at the upper and lower ends of the catalyst. After leak testing with nitrogen, the reaction system was heated and then the reaction raw materials were introduced. The reaction pressure was 0.75 MPaG and the volumetric space velocity was 2000 h -1 The raw gas phase composition is 40% propylene, 10.0% acetic acid, 7.0% oxygen, 33% nitrogen and 10% water. The reaction temperature is gradually increased to 157.2°C. The space-time yield of the catalyst is 388, which is equivalent to the normal evaluation of the catalyst for 4470 hours. The degraded catalyst was measured by transmission electron microscopy to count the grain sizes of 300 active components, with an average value of 10.2nm. The average grain size of the active components of the catalyst that is normally operated for 4470 hours is 10nm. The grain size of the degraded catalyst is basically consistent with the grain size of the catalyst after 4470 hours of normal evaluation.
[0061] [Comparative Example 1]
[0062] The catalyst is placed in a high temperature environment for treatment to accelerate the agglomeration of active components and the increase of grain size. This comparative example is used to compare the catalyst degradation method disclosed in the present invention.
[0063] 1) Catalyst degradation
[0064] 500 mL of fresh catalyst was taken and placed in a tubular fixed bed reactor. The catalyst was heated to 450° C. in a nitrogen atmosphere and treated for 50 h to obtain a degraded catalyst.
[0065] 2) Catalyst performance test
[0066] 500 mL of the degraded catalyst was placed in a fixed bed reactor with an inner diameter of 3 cm and a height of 150 cm. Inert porcelain balls were loaded at the upper and lower ends of the catalyst. After nitrogen leak testing, the reaction system was heated to 140 °C, and then the reaction raw materials were introduced. The reaction pressure was 0.75 MPaG and the volumetric space velocity was 2000 h -1 The raw gas phase composition was 40% propylene, 10.0% acetic acid, 7.0% oxygen, 33% nitrogen and 10% water. The reaction temperature was gradually increased to 140.7°C. The space-time yield of the catalyst was 384, which was equivalent to the normal evaluation operation of the catalyst for 576 hours, indicating that the catalyst did not have a significant deterioration effect after deterioration treatment.
[0067] [Comparative Example 2]
[0068] The normal operating temperature of the catalyst is increased to accelerate the deactivation of the catalyst. This comparative example is used to compare the catalyst deterioration method disclosed in the present invention.
[0069] 1) Catalyst degradation
[0070] 500 mL of the degraded catalyst was placed in a fixed bed reactor with an inner diameter of 3 cm and a height of 150 cm. Inert porcelain balls were loaded at the upper and lower ends of the catalyst. After leak testing with nitrogen, the reaction system was heated to 160 °C, and then the reaction raw materials were introduced. The reaction pressure was 0.75 MPaG and the volumetric space velocity was 2000 h -1 The raw gas phase composition is 40% propylene, 10.0% acetic acid, 7.0% oxygen, 33% nitrogen and 10% water, and the treatment is 50 hours.
[0071] 2) Catalyst performance test
[0072] The reaction temperature was gradually increased to 165.6°C, and the space-time yield of the catalyst was 373, which was equivalent to 5718 hours of normal evaluation of the catalyst. The degraded catalyst was measured by transmission electron microscopy to count the grain sizes of 300 active components, with an average value of 4.3nm. The average grain size of the active components of the catalyst that was normally operated for 5718 hours was 12.3nm. The grain size of the degraded catalyst was significantly different from that of the catalyst after 5718 hours of normal evaluation, indicating that the degradation method cannot truly simulate the degradation effect of the catalyst.
[0073] According to the above experimental results, compared with normal catalyst evaluation, catalyst degradation treatment greatly shortens the time for catalyst evaluation, reduces material consumption, reduces energy consumption, improves catalyst development efficiency, reduces catalyst development costs, and improves industry competitiveness.
[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A method for catalyst degradation, the method comprising the following steps: a) placing a fresh catalyst into a reactor, and introducing an organic acid, water and oxygen for treatment; b) Drying by passing inert gas; c) introducing C3-C6 olefin, acetic acid, water, inert gas and oxygen to react; d) introducing an inert gas and acetic acid to obtain a degraded catalyst.
2. The method for catalyst degradation according to claim 1, characterized in that: The fresh catalyst comprises a carrier, an active metal and an additive, wherein the chemical composition of the carrier is SiO2 and optionally Al2O3, Fe2O3 or a mixture thereof, and the catalyst active component comprises metal palladium and optionally gold, copper and tin; the additive is an alkali metal acetate, and preferably the alkali metal acetate is at least one of sodium acetate, potassium acetate and cesium acetate, and more preferably potassium acetate.
3. The method for catalyst degradation according to claim 1 or 2, characterized in that: The fresh catalyst has a palladium content of 0.5-10 g / L, preferably 1.0-6.0 g / L; a gold content of 0-8 g / L, preferably 0-5 g / L; a copper content of 0-5 g / L, preferably 1-3 g / L; a tin content of 0-3 g / L, preferably 0-2 g / L; and / or an alkali metal acetate content of 10-100 g / L, preferably 20-80 g / L.
4. The method for catalyst degradation according to any one of claims 1 to 3, characterized in that: In step a), the treatment is carried out at a reaction temperature of 100-300° C., preferably 120-200° C., and a pressure of 0.1-3 MPa, preferably 0.3-1.5 MPa.
5. The method for catalyst degradation according to any one of claims 1 to 4, characterized in that: The organic acid is selected from at least one of formic acid, acetic acid, propionic acid, acrylic acid, butyric acid, and succinic acid, preferably acetic acid; the oxygen can be added in the form of pure oxygen or in the form of air; the volume concentration of the organic acid is 1-25%, preferably 5-20%, the volume concentration of water is 1-25%, preferably 5-20%, the volume concentration of oxygen is 0.5-10%, preferably 1-8%, and the remaining gas is nitrogen; the treatment time is 5-100 hours, preferably 10-80 hours.
6. The method for catalyst degradation according to any one of claims 1 to 5, characterized in that: In step b), the inert gas is at least one of nitrogen, helium, argon and carbon dioxide, preferably nitrogen and carbon dioxide; the drying temperature is 100-200° C., and the treatment time is 0.5-8 h, preferably 1-6 h.
7. The method for catalyst degradation according to any one of claims 1 to 6, characterized in that: In step c), the C3-C6 olefin is at least one of propylene, isobutylene, butadiene, pentene and hexene, preferably propylene and isobutylene; the inert gas is at least one of nitrogen, helium, argon and carbon dioxide, preferably nitrogen and carbon dioxide.
8. The method for catalyst degradation according to any one of claims 1 to 7, characterized in that: In step c), the feed molar ratio of C3-C6 olefin: acetic acid: water: oxygen: inert gas is 20-70: 4-20: 0-20: 1-10: 20-60; the reaction temperature is 120-200°C, the treatment time is 2-10h, the reaction pressure is 0.1-1.5MPa, preferably 0.3-1.0MPa; the space velocity is 500-4000h -1 , preferably 600-2500h -1 . The method for catalyst degradation according to any one of claims 1 to 8, characterized in that: The inert gas in step d) is at least one of nitrogen, helium, argon and carbon dioxide, preferably nitrogen and carbon dioxide; the molar ratio of the inert gas to the acetic acid feed is 70-99:1-30.
Citation Information
Patent Citations
A catalyst, its preparation method and application
CN114054044B
Suppression of aging for PD-AU vinyl acetate monomer catalyst
CN1292726A